Greetings.
The answer is (5,4)
Step-by-step explanation:
Solving by elimination can be done by adding or subtracting of first and two equation.
Find any terms that make themselves = 0.
And that is the y-term.
Our 2y and -2y. If we add each others, we'd get 0 for y-term.
Therefore, we eliminate the y-term first.
![\left \{ {{-x+2y=3} \atop {3x-2y=7}} \right. \\2x=10](https://img.qammunity.org/2021/formulas/mathematics/high-school/7cs7rj4vu3avn3kycsrcewo40jgf1x0ds8.png)
If you are wondering how I get 2x = 10 then here's the explanation.
So we simply add/subtract both equations.
We do -x + 3x = 2x
Then +2y - 2y = 0
And 3 + 7 = 10
That's how we get 2x = 10.
Basically Add/Subtract in Vertical way.
![2x=10\\x=5](https://img.qammunity.org/2021/formulas/mathematics/high-school/ftlk1g872emmm6ayyyu53xcmim209i8t6r.png)
We may get the x-value but we need to know the y-value too.
Therefore, substitute x = 5 into any given equations. I suggest you to substitute the x-value in any equations with less coefficient value.
I'd rather substitute x = 5 in -x+2y = 3.
![-x+2y=3](https://img.qammunity.org/2021/formulas/mathematics/high-school/ph3r2afdffp9tv8a3585qb5mw4f4ecg3ap.png)
Substitute x = 5 in -x + 2y = 3
![-5+2y=3\\2y=3+5\\2y=8\\y=(8)/(2)\\y=4](https://img.qammunity.org/2021/formulas/mathematics/high-school/abwlckkgbcip2lb9icdky3tzi32gip1x3a.png)
Therefore, when x = 5, y = 4. Since you want the answer in ordered pairs then It's (5,4).